Clinical Significance of TIPE2 Protein Upregulation in Non-Hodgkin's Lymphoma. (September 2016) - Hao, Chunyan; Zhang, Na; Geng, Minghong; Ren, Qing; Li, Yan; Wang, Yan; Chen, Youhai H.; Liu, Suxia
Non-Hodgkin's lymphoma (NHL), which includes diffuse large B-cell lymphoma (DLBCL) and peripheral T-cell lymphoma, is a refractory malignant tumor originated from the lymphatic system. TNFAIP8L2 (TIPE2 or tumor necrosis-alpha-induced protein-8 like 2) is a negative regulator for inflammation and an inhibitor for carcinogenesis. However, whether TIPE2 plays a role in lymphomagenesis is unknown. In this study, we determined TIPE2 expression in NHL by immunohistochemistry and investigated its clinicopathological significance in DLBCL. We found that TIPE2 expression was upregulated in both DLBCL and peripheral T-cell lymphoma. But the expression of TIPE2 in T lymphomas was weaker than that in DLBCL. Interestingly, among DLBCL, TIPE2 expression was significantly stronger in the germinal center B-cell (GCB) type than in the non-GCB type. These results suggest that the expression of TIPE2 protein could be a predictor of better prognosis for DLBCL.